Strategic Information Systems Planning Of Public Sector In Economic Crisis: An Integrated Framework - Georgios I. Farantos; Nikitas Spiros Koutsoukis (European Scientific Journal, ESJ, 2016)
The purpose of the study is to establish a framework for the impact of strategic planning on the public sector's information systems during the economic crisis. The survey has been designed for the literature review of the strategic planning of information systems and the enrichment through the review of the effect on this economic crisis. The research methodology extends to the literature review of strategic planning of information systems and the creation of a framework for its implementation in an economic crisis. We approach the general concepts of Strategic Management and Policy Analysis and also the more specific ones of Strategic Planning of Information Systems. We note the relationship between strategy and crisis and the relationship between efficiency and strategic management in the economic crisis. Based on the results of the survey for the strategic planning of public sector information systems, we enrich the study with more specific crisis management and we create a new study framework. Useful conclusions for the integrated management of public sector information systems in crisis arise. The study is limited by the introduction of the economic crisis and cannot be generalised as such in a period of normal operation of the organisations. This original research leaves room for further study cases in the future and completion of the strategic planning studies of public sector IT systems during the economic crisis.